Institutional abuse toward the elderly: Perceptions of health care providers and older adult - M. Guadalupe Ruelas-González; Blanca Estela Pelcastre-Villafuerte; Hortensia Reyes-Morales (Instituto Nacional de Salud Pública, 2014)
Objective. To analyze the health care providers (HCP) and elderly patients' perceptions about abuse of the elderly by health personnel of public health services, in selected cities in Mexico. Materials and methods. A qualitative study and a strategy of data triangulation were performed during 2009 and 2012; 13 HCPs and 12 elders were interviewed, in order to obtain their experience regarding elder abuse. Grounded Theory proceedings were used for the analysis. Results. Elder abuse is a naturalized practice, from HCP and elderly people's point of view; these perceptions are showed in different ways. Conclusion. Institutionalization, historical professionalization and lack of consciousness about needs of the elderly (sociocultural and economic), require changes in planning, organization and monitoring process in the Health System; training and educational interventions on staff and exchange attitudes and behavior are necessary in order to offer a health care that is comprehensive, decent, human and with respect for the human rights.